The Application of Laswell Communication Model on The Good Message Within Religious Malay Films - Rosmawati Mohamad Rasit,; Muhamad Faisal Ashaari,; Salasiah Hanin Hamjah (USIM Press, 2024)
Vol. 33 No. 1 (2021): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences [April 2021]